1995
DOI: 10.1530/eje.0.1320497
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone (GH) modulates insulin-like growth factor I (IGF-I) and type I IGF receptor mRNA levels in the ovary of prepubertal GH-deficient rats

Abstract: In order to explore the potential role of growth hormone (GH) in modulating insulin-like growth factor I (IGF-I) gene expression in the prepubertal rat ovary, female rats were rendered GH deficient by neonatal administration of monosodium glutamate (MSG). One group of rats received vehicle and served as the control. At 21 days of age, MSG-treated rats received either GH or vehicle for 2 weeks. On days 21, 24, 28 and 31 animals were weighed and subsets were sacrificed for liver RNA extraction. The remaining ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…However, a recent study reported that ovarian levels of lGF-I mRNA were decreased in young rats made GH deficient by treatment with monoso dium glutamate. This effect was reversed by GH treatment (29). Similar to our findings, Samaras et al (30) reported that ovarian lGF-l mRNA levels were not altered in prepubertal gilts after 20 or 40 days of exogenous GH treatment in spite of increased levels of lGF-l in both serum and FFL.…”
Section: Discussionsupporting
confidence: 90%
“…However, a recent study reported that ovarian levels of lGF-I mRNA were decreased in young rats made GH deficient by treatment with monoso dium glutamate. This effect was reversed by GH treatment (29). Similar to our findings, Samaras et al (30) reported that ovarian lGF-l mRNA levels were not altered in prepubertal gilts after 20 or 40 days of exogenous GH treatment in spite of increased levels of lGF-l in both serum and FFL.…”
Section: Discussionsupporting
confidence: 90%
“…It is safe, with no side‐effects or contra‐indications, reproducible, unaffected by metabolic variables, such as free fatty acids, glucose, etc. (Dieguez & Casanueva, 1995; Maccario et al ., 1995; Malozowski et al ., 1995; Catalina et al ., 1998; De Marinis et al ., 2000), and explores the whole hypothalamus‐stalk‐pituitary axis (Pombo et al ., 1995; Popovic et al ., 1995). It is also unaffected by the GH levels at the begining of the test.…”
Section: Discussionmentioning
confidence: 99%
“…Em um sentido geral, a somatotrofina antagoniza a ação da insulina, porém, algumas vezes, sua ação é exercida de modo indireto via IGF-1, receptores e proteínas ligantes. Metabolicamente a somatotrofina é inibida pela hiperglicemia, por níveis crescentes de ácidos graxos e pela obesidade (NORMAN & LITWACK, 1987;MALOZOWSKI et al, 1995).…”
Section: O Objetivo Do Presente Estudo Foi O De Avaliar O Efeito Da Sunclassified